2020
DOI: 10.3390/nu12082429
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition and Depression in Older Adults Living in Nursing Homes in Mexico City

Abstract: This study evaluated the association between nutritional status, depressive symptoms, and the number of prescription drugs taken by older adults living in nursing homes in Mexico City. In a cross-sectional study, 262 participants were subjected to anthropometric and nutritional (Mini Nutritional Assessment (MNA)) evaluations; additionally, their depression (Geriatric Depression Scale (GDS)) and functional status were assessed. Multiple logistic regression was used for identifying factors associated with the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 51 publications
(71 reference statements)
4
30
0
3
Order By: Relevance
“…Firstly, the study group was restricted to Central-European community-dwelling older individuals therefore results may be different in other cultures. Correlations of nutritional status and depression may also be different in the institutionalized environments [ 51 , 52 ]. Secondly, no tests were conducted among people with severe dementia or those who were not able to present at the clinic due to mobility problems.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the study group was restricted to Central-European community-dwelling older individuals therefore results may be different in other cultures. Correlations of nutritional status and depression may also be different in the institutionalized environments [ 51 , 52 ]. Secondly, no tests were conducted among people with severe dementia or those who were not able to present at the clinic due to mobility problems.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies were not included in the meta-analysis so they were only used for qualitative summary: one study 22 used the same database as a study that was included in the meta-analysis; 23 three other studies reported data that could not be pooled because of the too-small number of articles (two studies reported the association between polypharmacy and depression as Pearson's correlation coefficient (r), 24,25 and the other study reported the number of medications used by depressed and nondepressed patients 26 ). All of the included studies were observational, 19 of them were cross-sectional, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and four of them were prospective cohorts. [40][41][42][43] The characteristics of the 23 articles are summarised in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A low intake of nutrient-dense foods places older adults at risk for malnutrition, especially protein and micronutrient deficiencies [ 11 , 21 ]. Furthermore, nutritional deficiencies, due to physiological changes (impaired mastication, swallowing, digestion, absorption, and utilization of nutrients); the presence of chronic diseases; and the influence of social and psychological factors [ 6 , 9 , 10 , 11 , 22 ] are even more pronounced in nursing homes, but are often neglected [ 23 , 24 ]. Nursing home residents (NHRs) are also more vulnerable to specific nutritional deficiencies because of the process of institutionalization itself, influencing food acceptance [ 25 ], eating habits, and behavior [ 26 ].…”
Section: Introductionmentioning
confidence: 99%